PENGARUH PRODUK, PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN MELALUI OJEK ONLINE (OJOL) PADA MASA COVID-19 DI KOTA YOGYAKARTA - Rakhmawati, Heru Noor; Affan, Junaidi (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2021)
The Purpose of this study was to determine the effect of product, promotion and service quality on purchasing decisions through online motorcycle taxis (ojol) during the covid-19 period in the city of Yogyakarta. Data collection techniques through interviews with data collection instruments in the form of questionnaries. This study uses quantitative analysis techniques using validity test, reliability test, classical assumption test, multiple linier regression analysis, coefficient of determination, significance test ( t test and F test). The result of the study obtained the result of the regression equation Y = 0,431+0,091X1+0,289X2+0,534X3, which means that product, promotion, and service quality affect purchasing decisions through online motorcycle taxis (ojol) during the covid-19 period in the city of Yogyakarta